IGF2BP3 enhances ferroptosis resistance in colon cancer by stabilizing SLC7A11 and is regulated by miR-98-5p - Sun, Yaya; Liu, Qingwei; Wu, Junjie; Jiang, Guangqing; Shi, Hongzhou; Zhang, Yihong; Ling, Yanxuan; Sun, Weimin; Shi, Xin; Liu, Congxing (Frontiers in Oncology, 2025)
PurposeColon cancer remains a global health challenge with rising mortality, necessitating novel therapeutic strategies. IGF2BP3, an oncogenic RNA-binding protein, is implicated in colon cancer progression, while its role in ferroptosis regulation remains unclear. This study investigates IGF2BP3’s role in ferroptosis regulation and its interplay with miR-98-5p in colon cancer, aiming to identify therapeutic targets for enhancing ferroptosis sensitivity.MethodsBioinformatics analyses (TCGA, UALCAN, GEPIA) assessed IGF2BP3 expression and prognostic relevance in colon cancer. The expression of IGF2BP3 in clinical samples were analyzed via immunohistochemistry (IHC) and Western blotting. IGF2BP3-knockdown (KD) cell lines (HCT116/DLD-1) were generated using lentiviral shRNA. Ferroptosis sensitivity was evaluated via CCK-8 assays, MDA/ROS quantification, and rescue experiments with ferrostatin-1. Transcriptomic sequencing, RNA immunoprecipitation (RIP), and RNA stability assays identified IGF2BP3-regulated targets. Dual-luciferase reporter assays validated miR-98-5p-IGF2BP3 interactions. Xenograft models assessed in vivo tumor growth.ResultsIGF2BP3 was significantly upregulated in colon cancer tissues and correlated with advanced T-stage, higher clinical stage, and poor survival (p<0.05). Knockdown of IGF2BP3 enhanced erastin-induced ferroptosis sensitivity, marked by elevated MDA and ROS levels, reversible by ferrostatin-1. Mechanistically, IGF2BP3 stabilized SLC7A11 mRNA via direct binding and SLC7A11 overexpression rescued ferroptosis resistance in IGF2BP3-KD cells. miR-98-5p directly targeted IGF2BP3’s 3′-UTR, suppressing its expression and enhancing ferroptosis sensitivity. In vivo, IGF2BP3-KD suppressed tumor growth and reduced Ki67/SLC7A11 expression.ConclusionIGF2BP3 drives ferroptosis resistance in colon cancer by stabilizing SLC7A11 mRNA, while miR-98-5p antagonizes this pathway via IGF2BP3 downregulation. Targeting the miR-98-5p/IGF2BP3/SLC7A11 axis offers a promising therapeutic strategy to enhance ferroptosis sensitivity and improve colon cancer outcomes.